The perception of the French /s/-/ʃ/ contrast in early Creole-French bilinguals - Dufour, Sophie; Kriegel, Sibylle; Alleesaib, Muhsina; Nguyen, Noël (Frontiers in Psychology, 2014)
One particularity of the Mauritian Creole language is that there is no contrastive distinction between the consonants /s/ and /ʃ/, which are both pronounced /s/ in Creole. In this study, we examined the identification performance of the /s/ - /ʃ/ contrast by Mauritian Creole-French bilinguals who have been exposed to French before 7 years of age, and who have been raised in a highly Creole-French bilingual society. The results showed that most of our bilingual participants identify the /s/ and /ʃ/ consonants like native French speakers. It also appeared that the way in which the two consonants are categorized can be manipulated by introducing subtle changes in the information these participants were given about the identity of the speaker that produced the stimuli. Our results are in accordance with recent studies showing native-like performance in bilinguals on a categorization task and, importantly, extend these findings to speakers of a Creole language. In addition, these results show that speech sound categorization can be influenced by information about the speaker's social identity and thus argue for models that postulate rich speech sound representations.